Gene delivery into mesenchymal stem cells: a biomimetic approach using RGD nanoclusters based on poly(amidoamine) dendrimers - Pandita, Deepti (2019)
Poly(amidoamine) dendrimers (generations 5 and 6) with amine termini were conjugated with peptides containing the arginine-glycine-aspartic acid (RGD) sequence having in view their application as gene delivery vectors. The idea behind the work was to take advantage of the cationic nature of dendrimers and of the integrin targeting capabilities of the RGD motif to improve gene delivery. Dendrimers were used as scaffolds for RGD clustering and, by controlling the number of peptides (4, 8, and 16) linked to each dendrimer, it was possible to evaluate the effect of RGD density on the gene delivery process. The new vectors were characterized in respect to their ability to neutralize and compact plasmid DNA (pDNA). The complexes formed by the vectors and pDNA were studied concerning their size, zeta potential, capacity of being internalized by cells and ability of transferring genes. Transfection efficiency was analyzed, first, by using a pDNA encoding for Enhanced Green Fluorescent Protein and Firefly Luciferase and, second, by using a pDNA encoding for Bone Morphogenetic Protein-2. Gene expression in mesenchymal stem cells was enhanced using the new vectors in comparison to native dendrimers and was shown to be dependent on the electrostatic interaction established between the dendrimer moiety and the cell surface, as well as on the RGD density of nanoclusters. The use of dendrimer scaffolds for RGD cluster formation is a new approach that can be extended beyond gene delivery applications, whenever RGD clustering is important for modulating cellular responses.